Growth Of Heterotrophic Bacteria At Sea Water Polluted By ‘Surf’ Detergent - Siti Ardiah; Dessy Yoswaty; Irwan Effendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Heterotrophic bacteria are decomposing bacteria that have an important role in maintaining the continuity of the life cycle of biota in the sea and as a standard of fertility in the waters. Heterotrophic bacteria obtain sources of food, oxygen and energy derived from the results of the decomposition process of the rest of other organisms, waste, or substances contained in the bodies of other organisms. This study aims to determine the effect of adding different concentration and duration of surf detergent to the growth of heterotrophic bacteria in sea water. This research was conducted from April to May 2018 using the experimental method. The results showed that the bacterial population in each treatment decreased with increasing concentration of detergent. The results showed that the highest number of heterotrophic bacteria was found at a concentration of 0.60% at station 1 exposure on the 10th day at 6.60 x 107 (CFU / ml) and 0.90% at the station on the 10th day of the day exposure the 10th was 6.72 x 107 (CFU / ml) and the lowest was found at a concentration of 0.90% on day 5 exposure at station 1 at 3.83 x 107 (CFU / ml). The value of the correlation coefficient (r) obtained is 0.177. Significant treatment of detergent concentration is different, which is equal to 0.00 <(0.550) and duration of exposure which is equal to 0.00 <α (0.45). Based on the results of this study, there is a negative effect of the addition of surf detergent with different concentration and duration of exposure to the growth of heterotrophic bacteria in seawater. Keywords: heterotrophic bacteria, Surf detergent.